Effects of Using EPS Geofoam as Compressible Inclusion on HDPE Pipe Behavior - Kilic, Havvanur; Akinay, Emre (ASCE-AMER SOC CIVIL ENGINEERS, 2019)
This paper presents the results obtained from an experimental study investigating the effects of using expanded polystyrene (EPS) as compressible inclusion on buried high-density polyethylene (HDPE) pipe behavior. A series of full-scale tests were conducted using a laboratory testing facility to investigate the effects of using EPS on the behavior of a 300-mm-nominal-diameter lined corrugated-wall HDPE pipe buried in a poorly graded sand medium. For this purpose, five different compressible inclusion geometries were designed. EPS with 10 kg/m3 nominal density was used as the compressible material. In order to simulate geostatic stresses imposed by shallow and high soil fills, vertical surcharge stresses up to 200 kPa were applied on surface of the burial medium. Comprehensive instrumentation was implemented in order to measure the pipe deflections, soil stresses on the pipe, and soil settlements in the pipe zone. In terms of performance and cost-efficiency, it is concluded that a single EPS panel above the pipe crown, which is as wide as one pipe outside diameter and as thick as 1/6 of pipe nominal diameter, offers the best solution. This solution provided a reduction in vertical stress at the pipe crown up to of 76% and in horizontal stress on the pipe walls at the springline up to of 65%. Vertical and horizontal pipe deflections are reduced by 87% and 60%, respectively, under 200-kPa surcharge stress. This solution also provided near-zero pipe deflections in the 100-125 kPa surcharge stress range.
Keywords: FIELD PERFORMANCE; EARTH PRESSURES; BOX CULVERTS; Engineering; Water Resources